VD_FINDINFO Décision / 2012 / 101 vom 14. November 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, CALOMNIE, DÉNONCIATION CALOMNIEUSE, DIFFAMATION | 14 CP, 173 ch. 2 CP, 173 CP, 174 ch. 1 CP, 179quater CP, 310 CPP (CH), 73 al. 2 CPP (CH)